EFEKTIVITAS KOMUNIKASI ANTARPERSONA DALAM DIVISI PRODUKSI PROGRAM BERITA ISLAMI MASA KINI TRANS TV - Arianti Wulandari; Bekti Istiyanto (Jurnal Ilmu Komunikasi Acta Diurna, 2014)
The success of interpersona communication shown by intimacy factor and equal minded indelivering a message between communican and communicator. Likewise also happen in BeritaIslami Masa Kini team that is broadcasted by TransTV. Needs to understanding the process ofinterpersonal communication will devide the success and continuity work as a target that will beteam’s responsibility. In order to make an effective communication between the members of theteam, interpersona communication choosed as a better way to deliver a message. Collecting datadue to this research is mainly on role observation, interview and literature study. The resultobtained described that a factor of proximity, the use of verbal and non verbal communication andmedium communication is the key in the success of interpersona communication in a team.